After the disclosure: measuring the short-term and long-term impacts of data breach disclosures on the financial performance of organizations. (8th April 2021) - Avery, Atiya
Abstract : Purpose: This study aims to evaluate changes to the financial performance of organizations in the 1–4 quarters following a data breach event. The study introduces two new variables, "intangible assets" and "extraordinary losses" to the discussion on the impact of data breaches on an organization's financial performance. Intangible assets allow us to gauge the data breach's impact on the organization's brand reputation and intellectual capital reserves. Extraordinary losses allow us to gauge if organizations considered data breaches truly detrimental to their operations that they rose to the level of "extraordinary" and not an event that could be incorporated into its usual operating expenses. Design/methodology/approach: This study uses a matched sample comparison analysis of 47 organizations to understand the short-term and long-term impacts of data breach events on an organization's financial performance. Findings: Data breach events have some negative impacts on the organization's profitability more than likely leading to a depletion of the organization's assets. However, organizations do not perform better or worse in the short-term or long-term due to a data breach event; the organizations can be considered financially sustainable in the 1–4 quarters following a data breach disclosure. Originality/value: This study takes two approaches to theory development. The first approach extends the current literature on data breach events as negative, value declining events to the organization's performance, which is referred to as the "traditional view." The second view posits that a data breach event may be a catalyst for enhanced long-term organization performance; this is referred to as the organizational sustainability and resiliency view.